THE REPRESENTATION OF MOVEMENT IN ART - Ruskule, Inga (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2018)
The aim of the article is to explore and analyze the movement representation methods in static artworks. Applied methods: Theoretical research and analysis of literature sources and Internet resources.Conclusion: Artists of different eras have turned to reproduce motion. Visual depiction is static, but it is possible to create the illusion of activity. Because movement occurs in time and space, the task of the artist is to model these dimensions on the artwork space so that it creates the impression of motion. Artists use the following ways of representing motion: creation of dynamic, energetic, asymmetrical and varied composition; expression; vagueness, uncertainty, blending; repetition of lines and shapes, image doubling, triplication etc.; representation of different motion positions, poses, gestures; a combination of various spaces and times; representation of such images, actions and places, which are associated with motion (vehicle, road, stairs etc.); use of opposites of motion and peace; etc.